Economic evaluation of non-invasive liver tests for the diagnosis of liver fibrosis in chronic liver diseases: A systematic review protocol - Cardoso, Marilia Mastrocolla de Almeida [UNESP]; Thabane, Lehana; Romeiro, Fernando Gomes [UNESP]; Silva, Giovanni Faria [UNESP]; Rugolo, Juliana Machado; Fonseca, Alan Francisco; Dos Santos, Wendel Mombaque; Almeida, Juliana Tereza Coneglian de; Thavorn, Kednapa; Tarride, Jean-Eric (Wolters Kluwer, 2024)
Objective: The objective of this review is to determine the costs and benefits of non-invasive liver tests vs liver biopsy in patients with chronic liver diseases. Introduction: Hepatic diseases can lead to liver fibrosis, cirrhosis, and hepatocellular carcinoma. In the past, liver biopsy was the only option for diagnosing fibrosis degree. Liver biopsy is an invasive procedure that depends on the sample size to be able to deliver an accurate diagnosis. In recent years, non-invasive liver tests have been increasingly used to estimate liver fibrosis degree; however, there is a lack of economic assessments of technology implementation outcomes. Inclusion criteria: This review will include partial (cost studies) and complete economic evaluation studies on hepatitis B, hepatitis C, alcoholic liver disease, and non-alcoholic fatty liver disease that compare non-invasive liver tests with liver biopsies. Studies published in English, French, Spanish, German, Italian, or Portuguese will be included. No date limits will be applied to the search. Methods: This review will identify published and unpublished studies. Published studies will be identified using MEDLINE (PubMed), Cochrane Library (CENTRAL), Embase, Web of Science, Scopus, and LILACS. Sources of unpublished studies and gray literature will include sources from health technology assessment agencies, clinical practice guidelines, regulatory approvals, advisories and warnings, and clinical trial registries, as well as Google Scholar. Two independent reviewers will screen and assess studies, and extract and critically appraise the data. Data extracted from the included studies will be analyzed and summarized to address the review objective using narrative text, and the JBI dominance ranking matrix.
Keywords: cost analysis; cost-effectiveness; health economic evaluation; liver fibrosis; non-invasive liver tests